H G Wells - Roberts, Adam. author. aut Link
XV, 452 p. 11 illus., 3 illus. in color.
Keywords: This is the first new complete literary biography of H G Wells for thirty years, and the first to encompass his entire career as a writer, from the science fiction of the 1890s through his fiction and non-fiction writing all the way up to his last publication in 1946. Adam Roberts provides a comprehensive reassessment of Wells’ importance as a novelist, short-story writer, a theorist of social prophecy and utopia, journalist and commentator, offering a nuanced portrait of the man who coined the phrases ‘atom bomb’, ‘League of Nations’ ‘the war to end war’ and ‘time machine’, who wrote the world’s first comprehensive global history and invented the idea of the tank. In these twenty-six chapters, Roberts covers the entirety of Wells’ life and discusses every book and short story he produced, delivering a complete vision of this enduring figure.